2009
DOI: 10.1111/j.1945-5100.2009.tb00783.x
|View full text |Cite
|
Sign up to set email alerts
|

The Carancas meteorite impact crater, Peru: Geologic surveying and modeling of crater formation and atmospheric passage

Abstract: It is the smallest, youngest, and one of two eye-witnessed impact crater events on Earth. The impact violated the hitherto existing view that stony meteorites below a size of 100 m undergo major disruption and deceleration during their passage through the atmosphere and are not capable of producing craters. Fragmentation occurs if the strength of the meteoroid is less than the aerodynamic stresses that occur in flight. The small fragments that result from a breakup rain down at terminal velocity and are not ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 36 publications
0
41
0
Order By: Relevance
“…(); (3) Kenkmann et al. (); (4) Miura and Kato (); (5) Kofman et al. (); (6) This work; (7) Dietz (); (8) Smith and Hodge (); (9) Bunch and Cohen (); (10) Chao et al.…”
Section: Discussionmentioning
confidence: 96%
“…(); (3) Kenkmann et al. (); (4) Miura and Kato (); (5) Kofman et al. (); (6) This work; (7) Dietz (); (8) Smith and Hodge (); (9) Bunch and Cohen (); (10) Chao et al.…”
Section: Discussionmentioning
confidence: 96%
“…With the proposed impact angles, velocities, and meteoroid and target material properties it is possible to estimate the radius of the meteoroid at the time of impact. In a manner similar to that of Kenkmann et al. (2009), scaling laws based on the theoretical analysis of cratering mechanics by Holsapple and Schmidt (1987), Housen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the recent impact of the Carancas H chondrite, which produced a 14 m wide crater in Peru, showed that the atmospheric fragmentation process may be strongly dependent on entry velocity and angle, in addition to physical strength (Kenkmann et al. 2009).…”
Section: Mass Distribution Of Que 90201 Showermentioning
confidence: 99%